On liskovets approach for nonlinear ill-posed problems under arbitrarily perturbative operators - Bường, Nguyễn (Journal of Computer Science and Cybernetics, 2016)
The purpose of this paper is to present a modification of Liskovets’s approach of solution of nonlinear ill-posed problems involving monotone operators in real reflexive Banach space under arbitrarily perturbative operators. The aspect of convergence of Tikhonov regularization is considered in combination with finite-dimensional approximations of the space.